New Cytotoxic Benzonitrile Glycosides from Brugmansia arborea Flowers - Kim, Hyoung‐Geun; Ko, Jung‐Hwan; Oh, Hyun‐Ji; Song, Hae Seong; Kwon, Jung‐Hwa; Lee, Yeong‐Geun; Lee, Dae‐Young; Kang, Sae‐Chan; Baek, Nam‐In (Bulletin of the Korean Chemical Society, 2018)
KCI Citation Count: 5